(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2019)
The purpose of the research is to clarify the role played by the audit committee of private Syrian banks and its importance to improve the internal control system, which is important and necessary for both management and stakeholders in banks, from the point of view of internal auditors in private banks. The research was based on the analytical descriptive approach. A questionnaire was prepared and developed containing questions related to the study aspects. The questionnaire was distributed to a sample of internal auditors working in internal audit departments in private banks in Syria. ), While Islamic banks were excluded as they were subject to the Shari’a Audit Department. Accordingly, 48 questionnaires were distributed to all auditors in the internal audit departments of the private banks. Forty- 85.42%). The study found that there is great support for the activities of the Audit Committee and lead to improvement of the internal control system and its effectiveness in the Syrian private banks sample of the study, with relative importance (68.86%). This means that the Audit Committee plays an important role in improving the internal control system Activities. يهدف البحث إلى بيان الدور الذي تؤديه لجنة التدقيق في المصارف السورية الخاصة, وأهميته لتحسين نظام الرقابة الداخلية التي تعد أمراً مهماً وضرورياً لكل من الإدارة وأصحاب المصالح في المصارف, وذلك من وجهة نظر المدققين الداخليين في المصارف الخاصة. اعتمد البحث على المنهج الوصفي التحليلي, حيث تمّ إعداد وتطوير استبانة تتضمن الأسئلة المتعلقة بجوانب الدراسة, وتمّ توزيعها على عينة من المدققين الداخليين العاملين في إدارات التدقيق الداخلي في المصارف الخاصة في سورية, والبالغ عددها (14) مصرف خاص, حيث استهدف البحث الحالي (11) مصرف, بينما تمّ استبعاد المصارف الإسلامية, كونها تخضع لإدارة التدقيق الشرعي (وفق أحكام الشريعة الاسلامية), وبناءً على ذلك تمّ توزيع (48) استبيان على كافة المدققين في إدارات التدقيق الداخلي في المصارف الخاصة, واسترجع منها (41) استبيان بنسبة استجابة (85.42%). توصل البحث إلى أنّ هناك تأييد كبير للأنشطة التي تمارسها لجنة التدقيق وتؤدي إلى تحسين نظام الرقابة الداخلية وفعاليته في المصارف السورية الخاصة عينة الدراسة, وبأهمية نسبية (68.86%), مما يعني أنّ لجنة التدقيق تؤدي دوراً مهماً في تحسين نظام الرقابة الداخلية وفعاليته عندما تمارس هذه الأنشطة.